Sperm RNA preparation for transcriptomic analysis: Review of the techniques and personal experience. (6th March 2017) - El Fekih, S.; Nguyen, M.‐H.; Perrin, A.; Beauvillard, D.; Morel, F.; Saad, A.; Ben Ali, H.; De Braekeleer, M.
Summary: In the last 10 years, several approaches, including microarrays, have been applied to investigate sperm transcript levels. However, success using microarray profiling is highly dependent of the quality of the RNA obtained. Therefore, the development of methods that deliver highly purified and intact RNA is of utmost importance. The three steps used to achieve this goal, purification of spermatozoa, RNA extraction and evaluation of RNA quality, are reviewed. Following that review and preliminary experiments, we processed sperm samples from seven normozoospermic men with a combination of gradient centrifugation and somatic cell lysis. RNA was extracted using the NucleoSpin RNA XS kit (Macherey‐Nagel) and its purity checked using the BioAnalyzer. Hybridisation was done on Agilent SurePrint G3 Human GE 8 × 60K V2 microarrays. We identified 900 transcripts among the 1000 high abundance sperm transcripts reported in the literature. These genes are known to be involved in several biological processes, notably spermatogenesis, transcription regulation, cell growth and differentiation, sperm motility and capacitation, fertilisation, and embryogenesis. Therefore, our methodology is highly suitable for sperm transcriptomic analyses and can be used, notably, to compare mRNA profiles between fertile and infertile males.